TANTANGAN PLAGIARISME DALAM BUDAYA PENULISAN KARYA TULIS ILMIAH - Ervina Yunita; Henri Prianto Sinurat; Rati Sumanti (Puslatbang KHAN, 2021)
Until now, scientific writing has not been free from plagiarism behavior. Plagiarism is the act of copying or using someone else's work without revealing the identity of the owner. Plagiarism is an act that is strictly prohibited in academia. The perpetrators of plagiarism come from beginner writers to academics who actually understand the ethics of writing scientific papers. This research has mapped the challenges in writing scientific papers. This study uses qualitative methods with data collection techniques through interviews, document review and observation. The goal is to find a solution to prevent the development of plagiarism in the preparation of scientific papers. The factors driving the development of a culture of plagiarism are influenced by the availability of information via the internet which is very easy; strong pressure for academic publications and requirements for career paths; lack of confidence and writing skills among novice writers; limited time in compiling scientific papers; lack of understanding of the author regarding plagiarism. To minimize the occurrence of plagiarism, it can be done by searching for references on the internet properly, fulfilling publication obligations in the academic realm, collaboration in writing, increasing writing reference sources, increasing writing competence, using information and communication technology.